Morphological papameters of stomata and the cuticular waxes composition of silver linden (Tilia tomentosa Moench) leaves under conditions of lighting and shading - Yu.V. Lykholat; N.O. Khromykh; A.A. Alekseeva; O.I. Serga; B.E. Yakubenko; I.P. Grigoryuk (Інтродукція Рослин, 2017)
Objective – to determine the differences in the morphological parameters of stomata and the component composition of cuticular waxes of silver linden (Tilia tomentosa Moench) leaves under conditions of lighting and shading in the crown of a tree.